Product feature and lifespan as a quality indicator for inducing eco-friendly furniture purchase - Md. Mahiuddin Sabbir (Heliyon)
Limited understanding exists of the underlying mechanisms triggering consumers' decisions to purchase Engineered Wood Furniture (EWF), particularly regarding product quality (PQ), which has typically been viewed as a unidimensional construct, neglecting its multidimensional nature. This study, therefore, captures the dimensions of PQ and identifies how environmental concerns and subjective norms interact with PQ to stimulate consumers' adoption of EWF. Analyzing data from 390 respondents, the study confirms that product features and lifespan are crucial components of PQ, directly and indirectly impacting positive attitudes and purchase intentions toward EWF. Moreover, the moderation and moderated mediation results manifested the criticality of subjective norms and environmental concerns in eliciting greater favorable attitudes and purchase intentions toward EWF based on PQ. Drawing on these theoretical contributions, the study suggests leveraging the environmental benefits of EWF in promotional activities and leveraging subjective norms through social endorsements and online communities to encourage consumers’ adoption of EWF.